MENGURANGI HARMONISA PADA TRANSFORMATOR 3 FASA - Irianto, Chaerul Gagarin; Sukmawidjaja, Maula; Wisnu, Aditya (Jurnal Teknik Elektro, 2008)
Consumption of the electronic devices has been increase in the late of twenty years recentlyand it will cause the problem which had been unexpected before. It will cause non sinusoidalcurrent, although it is supplied by sinusoidal voltage source. This current will interfere thehigh frequent component at power system distribution grid and then it called âharmoniccurrentâ. The harmonic current can cause a lot of trouble to the consumer even powerprovider as well. High cost operation, short lifetime any equipment as the most disadvantageif the harmonic current appear on electric power distribution system. There are manymethod to reduce the harmonic distortion. This papert will explain the use of Z transformerwith resonance arm filter to reduce harmonic distortion on the system.Keywords: Harmonic current, threephase transformer, Z transfor